(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Education is one of the most important tools of empowering Santal women. This paper analyse the current educational status of Santal women and role of education in social empowering of Santal women at Birbhum,West Bengal. Present paper compared the empowering status among the Santal Women at Patharghata, Bergram and Ballipara of Birbhum, West Bengal.